2004
DOI: 10.2172/15009859
|View full text |Cite
|
Sign up to set email alerts
|

Recent Site-Wide Transport Modeling Related to the Carbon Tetrachloride Plume at the Hanford Site

Abstract: Executive SummaryThe Hanford Carbon Tetrachloride Innovative Treatment Remediation Demonstration (ITRD) Program provided an initial evaluation of the nature and extent of carbon tetrachloride contamination in the unconfined aquifer in the 200 West Area of the Hanford Site. After the ITRD program ended, subsequent studies more closely examined the transport of carbon tetrachloride (CCl4) in the unconfined aquifer system. Those studies were undertaken to support strategic planning and provide guidance for the mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2005
2005
2008
2008

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 3 publications
0
2
0
Order By: Relevance
“…Previous fate and transport studies have demonstrated that the abiotic degradation of carbon tetrachloride and partitioning to aquifer sediments are the two parameters where uncertainty in the parameter values most significantly affect the fate and transport of carbon tetrachloride Bergeron and Cole 2005). In these studies, both Monte Carlo simulations for one-dimensional transport modeling and directed studies using a three-dimensional model concluded that the range of potential abiotic degradation rates (i.e., homogeneous hydrolysis) includes values that would result in attenuation of the carbon tetrachloride plume such that natural attenuation would be an important component of the remedy along with active remediation.…”
Section: A1 Abiotic Degradation Mechanisms Relevant For Carbon Tetramentioning
confidence: 99%
“…Previous fate and transport studies have demonstrated that the abiotic degradation of carbon tetrachloride and partitioning to aquifer sediments are the two parameters where uncertainty in the parameter values most significantly affect the fate and transport of carbon tetrachloride Bergeron and Cole 2005). In these studies, both Monte Carlo simulations for one-dimensional transport modeling and directed studies using a three-dimensional model concluded that the range of potential abiotic degradation rates (i.e., homogeneous hydrolysis) includes values that would result in attenuation of the carbon tetrachloride plume such that natural attenuation would be an important component of the remedy along with active remediation.…”
Section: A1 Abiotic Degradation Mechanisms Relevant For Carbon Tetramentioning
confidence: 99%
“…Previous modeling analysis suggests that these mechanisms may significantly reduce concentrations within the plume and decrease the extent of carbon tetrachloride plume migration (Truex et al 2001;Bergeron and Cole 2005). Natural attenuation processes acting on trichlorethene include sorption, dispersion, and dilution.…”
Section: Whether the Contaminants Present In Soil Or Groundwater Can mentioning
confidence: 99%